RANCANG BANGUN MODEL MONEV PENDIDIKAN KARAKTER - Listiyaning Sumardiyani; Ngurah Ayu Nyoman Murniati; Fine Reffiane (Universitas PGRI Semarang, 2015)
PGRI Semarang universities develop character education in every interaction both academic and non-academic. Strengthening these characters contained in Catur Dharma of the University, imitation. Based on the above, do research designing monitoring and evaluation of the model-based imitation of character education for the academic community of the PGRI Semarang University. This study uses R & D.Design based on the indicators set out in the imitation contained four components, namely the character of self-awareness, social awareness, self-management, and social skills. This model describes the monitoring and evaluation of imitation-based character education are implemented in an integrated manner. Suitability monitoring and evaluation design, implementation monitoring and evaluation, and monitoring and evaluation instrument of accession with the activities of the academic community into the main direction of this model.Research recommendations are given to the agencies to be able to change the conceptual model into a contextual model